Southwest Research-Extension Center, Field Day 1997 (Kansas Agricultural Experiment Station Research Reports, 1997)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: 1997; SRP789; crops; tillage; irrigation; insect control; weed science